Sistem Pendukung Keputusan Pemilihan Indekos Terbaik di Sekitar Universitas Harapan Medan Menggunakan Metode TOPSIS - Muhammad Fitra Abdillah; Haida Dafitri (Forum Kerjasama Pendidikan Tinggi, 2023)
Harapan Medan University is one of the universities located in the city of Medan, students who study not only come from within the city but there are also those from outside the region. Students who come from outside the region must have a temporary residence or boarding house, but due to limited information, students have difficulty finding boarding houses. Based on the existing problems, a boarding house selection system is built that can select and recommend the best boarding house. With this system, it is easier for students who come from outside the region to choose boarding houses according to the desired criteria. The decision support system built using the TOPSIS method where the TOPSIS method will produce a preference value for each boarding alternative data based on the weight value of the boarding criteria such as: price, distance, facilities, security, and chasitity. TOPSIS uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the farthest from the negative ideal solution by using the Euclidean distance to determine the relative closeness of an alternative to the optimal solution. The implementation of the system is carried out using the PHP programming language and MySQL as the database. The decision support system that is built produces recommendations by providing a ranking of boarding houses according to their preference values. Of the 10 boarding houses tested, the best alternative data is Kost Belpon Residence with a preference value of 0.8017 and followed by Kost Ungu with a preference value of 0.6653.